Taxonomic Reevaluation of the Polylepis sericea Complex (Rosaceae), with the Description of a New Species - Boza Espinoza, Tatiana Erika (2019)
The taxonomically difficult genus Polylepis (Rosaceae) contains several problematic species complexes, including one around P. sericea. We here reevaluate species boundaries in this complex based on morphological characters and climatic niches. We recognize five species within the P. sericea complex, based primarily on leaf characters: P. albicans (northwestern Peru), P. argentea (central Peru) described here, P. canoi (southeastern Peru to central Bolivia), P. ochreata (Ecuador to southernmost Colombia), and P. sericea (Venezuela to central Colombia). We provide full synonymy, diagnostic notes, lists of selected specimens examined, and a key to the species of the complex.